All-pass filter application using electronically tunable DDCC - (:unkn) unknown (IEEE Computer Society, 2014)
In this study, an electronically tunable differential difference current conveyor is presented. The benefits of this new active element are demonstrated on tunable first-order voltage-mode all-pass filter employing a resistor and a capacitor. In the proposed filter structure using single active and two passive elements no element-matching restriction is required. The theoretical results are verified with SPICE simulations using TSMC 0.35 μm CMOS process parameters and with ±2.5 V supply voltages. © 2014 IEEE.
Keywords: All-pass; Analog filters; Current conveyor; E-DDCC; Electronically tunable differential difference current conveyor; First-order; Voltage-mode